Public Administration Science in the Development of Digital Technology - Anak Agung Gde Brahmantya Murti (Journal of Contemporary Public Administration, 2021)
The rapid development of digital technology is considered the fourth industrial revolution causing various changes, especially in the science of state administration. By using a qualitative approach, this paper explains how the direction of the development of state administration in Indonesia is currently in the flow of technological change and what challenges it faces. Seeing from the history of the paradigm shift that occurred in the science of state administration, the focus and locus of this science is very important because it can affect the perspective of the development of the science of state administration. The rapid development of technology is feared to be able to shift the central role of humans. For this reason, scientists are required to be able to contextualize the science of state administration and at the same time utilize digital technology to answer the public interest